DECODING BOTS OF TERRORISM IN BALOCHISTAN (Margalla Papers, 2024)
Since the withdrawal of the US / North Atlantic Treaty Organization (NATO) forces from Afghanistan in August 2021, Balochistan has experienced a renewed wave of terrorism with improved organisational/operational capabilities and better-equipped Balochistan Liberation Army (BLA) and Balochistan Liberation Front (BLF). The information environment of Balochistan has also undergone a rapid change in the last three years, with the Baloch population, especially the Baloch youth, becoming more accessible to the Baloch Nationalist Militant Organizations through a very efficient militant narrative creation dissemination system. This system of narrative creation based on the manipulation of facts and fabricated stories matched by a dynamic propaganda dissemination system is quickly replacing the facts with an alternative reality. It has also successfully replaced the national mainstream media and is becoming an alternative media choice for the Baloch population. The Baloch Nationalist Militant Organisations’ narrative has quickly gained popularity among domestic audiences and accrues credence from international media. An effective response mechanism is crucial to counter the far-reaching implications through a comprehensive and all-encompassing national effort. Bibliography EntryIqbal, Jehanzeb. 2024. "Decoding Bots of Terrorism in Balochistan." Margalla Papers 28 (2): 63-77.